SIFAT PULP SODA ANTRAKINON KAYU AKASIA (ACACIA MANG/UM WILLD.) DAN AGATHIS (AGATHIS DAMMARA RICH) - Kayano Purba; Putritjatur Budilistyani; Surdiding Ruhendi; Rena M Siagian (Jurnal Penelitian Hasil Hutan, 1989)
The  anthraquinone   soda pulping   trials have  been  conducted   by  using Acacia  mangium   Willd. and Agathis  dammara Rich  woods  to  investigate  the  effect   of  anthraquinone   and  its optimum  usage on  the pulp  properties.   The pulping  trials have   been   conducted    individually    in a.    rotary  digester   using  soda  process,   with   16% of  active  alkali,  wood   to  liquor ratio  1    :   4,  maximum    temperature   170°C   and  keeping   the  maximum   temperature   for  two  hours   The  anthraquinone catalyst  was given in five  levels, namely  0.00,  0.05,  0.10,  0.15 and 0.20% of  the  weight  of oven  dry basis wood.The  result  of  the  investigation   showed   that  the  variation  in anthraquinone    used had a significant  effect on the pulp yield,   tear  strength, tear index, stretch  and permanganate   number   of  the pulp  from  Acacia  mangium  wood.   By  adding the same  catalyst  in the pulping   trials of  Agathis dammara  wood  it was found  that such  treatment   had a significant  effect on   the  pulp   yield,    tear  strength,    tear  index,   tensile  strength,    tensile  index,   breaking  length,  folding   endurance,    and bursting  strength.It  was found   that  the addition   of  anthraquinone catalyst   tended  to  increase  of  the pulp  yield  of  Acacia  mangium and   Agathis   dammara,  and  to  decrease  the  permanganate    number   of   the  pulp   of  Acacia  mangium.   In  general,   the addition   of  anthraquinone   catalyst  is increasing  the physical  properties   of  both   wood  species,  but  decreasing the bursting strength   of  the  Agathis  dammara  putp.Compared   to  the classification   of  hardwoods.  from   tropical   forest   according   to  Misra,  based  on  the  pulp   yield, alkali  consumption,    permanganate    number,   and  stretch,    the  Acacia  mangium   pulp   could  be  categorized   as   the  first quality   class,  based  on  the  breaking  length  as the second  quality   class, and  based on  the folding  endurance   it could  be categorized  as the  third  or fourth   quality  class. The optimum  cooking  condition   of Acaciamangium  was obtained  by add- ing of  0.05%  of  anthraquinone   catalyst. The  optimum  cooking   condition   of  Agathis  dammara   was obtained   with  0.10%   anthraquinone   catalyst.  Based  on the  Indonesia  Industrial  Standard   (Sll.08030-83),   at  this  level.  the  resulting pulp  can subsitute   the  unbleached  sulphate pulp  from  conifer wood.